THE COMMODIFICATION OF CHILDREN ON SOCIAL MEDIA: Exploring Child Exploitation through Hadith and Islamic Parenting Ethics - Shinta Nuriyah Hadiana; Zamzami, Mukhammad; Muhammad Lutfi; Wael Hegazy (Islamuna: Jurnal Studi Islam, 2025)
The phenomenon of child exploitation on social media shows an alarming escalation, especially when childrenâ€”even infantsâ€”are actively involved in the production of digital content to attract public sympathy or financial gain. This study analyzes child exploitation practices through a netnographic approach, focusing on a viral case of an orphanage in Medan that exploited children for live streaming on TikTok to obtain donations. Through stages of investigation, interaction, immersion, and integration, this research evaluates audience responses, digital interaction dynamics, and the psychological impact on children. Findings indicate that this exploitation blurs the boundaries between private and public spaces in children’s lives and normalizes the commodification of children in the digital economy. From an Islamic perspective, these actions contradict the ethical principles of parenting taught by the Prophet Muhammad, which emphasize love, protection of dignity, and the spiritual responsibility of parents. Thus, the prophetic values in parenting hadiths can serve as an ethical foundation for building fair, humane, and Islam-compliant digital parenting practices.